2019
DOI: 10.3390/su11236533
|View full text |Cite
|
Sign up to set email alerts
|

Learning from the Experiences of the Intergovernmental Panel on Climate Change: Balancing Science and Policy to Enable Trustworthy Knowledge

Abstract: To create a societal change towards a sustainable future, constructive relations between science and policy are of major importance. Boundary organizations such as the Intergovernmental Panel on Climate Change (IPCC) have come to play an important role in establishing such constructive relations. This study contributes to the development of empirically informed knowledge on the challenge of balancing different expectations for how the science–policy relation is to be constructed to create trustworthy knowledge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 62 publications
(141 reference statements)
1
5
0
Order By: Relevance
“…Looking behind these contestations and resonating with previous findings (Bickerstaff et al 2010; Chilvers 2008; Korinek and Veit 2015; Gustafsson 2019), we can see that despite prominent participatory rhetoric, a normal, or modern view of science and decisionist understanding of risk analysis persists. Particularly actors from the scientific, political, and corporate realm seem to hold strong interests in maintaining an image of independent, objective, and reliable scientific processes.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Looking behind these contestations and resonating with previous findings (Bickerstaff et al 2010; Chilvers 2008; Korinek and Veit 2015; Gustafsson 2019), we can see that despite prominent participatory rhetoric, a normal, or modern view of science and decisionist understanding of risk analysis persists. Particularly actors from the scientific, political, and corporate realm seem to hold strong interests in maintaining an image of independent, objective, and reliable scientific processes.…”
Section: Discussionsupporting
confidence: 66%
“…Looking at the wider discourse, this gives rise to an increasing contestation of different "institutional logics" (Greenwood et al 2011) where calls for greater participation meet the maintenance of an image of independent, objective, and reliable science and strategically as well as normatively grounded criticism of current and (potential future) engagement practices. Similar to other hybrid or boundary organizations, such as the Intergovernmental Panel on Climate Change (Gustafsson 2019) or the UK Food Stand Standards Agency (Rothstein 2013), this poses significant challenges for BfR in constructing its legitimacy and reputation.…”
Section: Discussionmentioning
confidence: 99%
“…Without access to the original code, the results of model-based science cannot be fully evaluated in peer review, which has repercussions for the “reproducibility crisis” in science and erodes public trust ( 7 ). An important reason that the 2009 so-called "climategate” affair (resulting from the hacking and release of emails by climate researchers at the University of Southampton, UK) had such a negative impact on public confidence in climate science was the lack of scientific transparency, including restricted access to climate models and data sets ( 8 , 9 ). This is somewhat ironic because climate models have some of the most rigorously tested and reliable scientific code ( 10 ).…”
Section: Models and Open Sciencementioning
confidence: 99%
“…Underlying this notion is the prevailing dominance of a linear model of the relationship between science and society. The empirical evidence of increased public trust in science due to public engagement is accordingly interpreted as mixed (164); there may be rhetorical support for public participation, yet it is also found that the public and stakeholders sustain a view of trustworthy science as being neutral and independent from political and societal interests (134,164,165). The rise of a post-truth era has accentuated this paradox and has accelerated attacks on environmental science as well as other contentious issues, such as vaccines; simultaneously, what should be seen as publicly accessible facts have fallen prey to appeals to emotions and personal belief.…”
Section: The Dark Side Of Co-production and The Crisis Of Expertisementioning
confidence: 99%